Impact of integrated crop management practices on productivity, profitability and energy budgeting of mustard in South-Eastern Rajasthan (Journal of Oilseed Brassica, 2026)
In the present study impact of integrated crop management (ICM) practices of mustard were studied at 225 farmers’ fields in heavy soils of South-Eastern Rajasthan during 2019-20 to 2021-22. Baseline information and soil fertility status of the area were collected before organizing cluster front line demonstrations (CFLDs), and then after demonstrated ICM practices recommended by Agriculture University, Kota (Rajasthan). It is evident from results that the yield of mustard in ICM plots was ranged between 2.31-2.36 t/ha which was higher over the farmers practice (FP). Similarly, ICM plots recorded higher gross returns (Rs.129780-154995/ha), net returns (Rs.102100-122445/ha) and B:C ratio (3.51-3.76). Whereas, ICM plots recorded lower energy input (11.95%) and cost of cultivation (5.45%) over the FP. Thus, adoption of ICM practices enhanced the productivity, profitability and can save input energy consumption substantially over the existing farmer’s practices of mustard cultivation.